Common Pathogens Involved in Causing Bovine Mastitis - Ashish, Ashish; Sengar, G.; Singh, Rani; Singh, Umesh; Kumar, Sushil; Deb, Rajib (Indian Farming, 2015)
Mastitis is the greatest impediment in achieving increased clean milk production, caused by various bacterial and fungal pathogens.Understanding the cause of mastitis and the causal agents helps in removing the severe infection in cows through proper treatment.